(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to analyze the budget impact of treating cardiovascular diseases at Le Van Thinh Hospital (LVT Hospital) from 2018 to 2023. Subjects and methods: A cross-sectional descriptive study was conducted through a retrospective review of data related to cardiovascular disease treatments at LVT Hospital during the 2018-2023 period. The budget impact was analyzed through the total healthcare costs covered by health insurance each year, categorized by disease groups, inpatient/outpatient treatments, and cost components. Data were processed and compiled using Excel, and analyzed with R software. Results: From 2018 to 2023, health insurance covered 85.0% of the total treatment costs for 746,159 treatment visits for cardiovascular diseases at LVT Hospital. Outpatient treatments accounted for 85.2% of the costs for 735,194 visits, while inpatient treatments accounted for 14.8% of the costs for 10,965 visits. Across the entire hospital, 81.2% of the costs were concentrated on treating hypertension, predominantly on outpatient care. In inpatient treatment, nearly 50% of the costs were equally divided between cerebrovascular diseases (25.1%) and hypertension (21.9%). The average cost per outpatient cardiovascular treatment visit increased over time (from VND 399,900 per visit in 2018 to VND 572,000 per visit in 2023). Medications accounted for 74.9% of the total treatment costs across the hospital. Laboratory and imaging costs were divided in a 2:1 ratio between outpatient and inpatient treatments, respectively. Conclusion: The information provided by this study will help hospital management comprehensively assess the use of hospital financial resources in treating cardiovascular diseases, thereby facilitating necessary interventions to optimize treatment costs.